2006
DOI: 10.1364/oe.14.008127
|View full text |Cite
|
Sign up to set email alerts
|

Harmonically-related diffraction gratings-based interferometer for quadrature phase measurements

Abstract: Abstract:We demonstrate the use of shallow diffraction gratings for quadrature phase interferometry. A single shallow diffraction grating-based Michelson interferometer yields only trivial (0 o or 180 o ) phase shift between different output ports. In comparison, a combination of two parallel shallow diffraction gratings can be useful to achieve desired phase shifts (e.g., 90 o for quadrature phase interferometry). We show that the phase at different output ports of a grating-pair based interferometer can be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

6
2

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 24 publications
0
14
0
2
Order By: Relevance
“…As is well known, a grating can confer additional phase shifts to the diffracted beams. For a shallow grating, the phase shifts can be written as [15] ] 2…”
Section: G1g2 Interferometery Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…As is well known, a grating can confer additional phase shifts to the diffracted beams. For a shallow grating, the phase shifts can be written as [15] ] 2…”
Section: G1g2 Interferometery Conceptmentioning
confidence: 99%
“…Recently, our group demonstrated a full-field phase imaging technique based on the substitution of a beamsplitter with a harmonically matched diffraction grating pair (G1G2 grating) [14,15] in an interferometer -we named the technique G1G2 interferometry. With this optical element substitution, we were able to create a non-trivial phase relationship between the different output ports of the interferometer.…”
Section: Introductionmentioning
confidence: 99%
“…We recently demonstrated that a quadrature free-space phase interferometer, termed as the G1G2 interferometer, can be created with a pair of harmonically matched shallow diffraction gratings. 5 In this letter, we report the following: ͑1͒ the creation of the harmonically matched grating pair on a single holographic plate, ͑2͒ the use of this single optical element in place of a beam splitter in a modified Mach-Zehnder interferometer and the observation of nontrivial phase between the outputs, and ͑3͒ a demonstration of full field phase imaging, which additionally illustrates the utility of phase imaging for flow dynamics studies.A single shallow diffraction grating can be used to create a multiport ͑n ജ 3͒ interferometer. However, the outputs of such an interferometer are trivially related in phase.…”
mentioning
confidence: 94%
“…Previously, we have developed a full-field phase imaging technique based on a harmonically matched diffraction grating pair (G1G2 grating) 15,16 . The grating is used as a beam splitter in a Mach-Zehnder interferometer to confer nontrivial phase shift between the two output ports of the interferometer.…”
Section: Introductionmentioning
confidence: 99%